Experimental Research on the Influence of Repeated Overheating on the Thermal Diffusivity of the Inconel 718 Alloy - Elisabeta Roxana Ungureanu Arva; Marioara Abrudeanu; Denis Aurelian Negrea; Andrei Galatanu; Magdalena Galatanu; Alin-Daniel Rizea; Daniel-Constantin Anghel; Mihai Branzei; Alexandra Ion Jinga; Mircea Ionut Petrescu (Applied Sciences, 2024)
The Inconel 718 superalloy, a precipitation-hardenable material, is of particular interest for applications involving components operating under extreme conditions due to its excellent mechanical properties, high corrosion resistance at temperatures up to 700 °C, and good workability. At high temperatures, thermal transfer processes are crucial for temperature distribution across the component’s section, structural transformations, and variations in the alloy’s properties. The history of accidental overheating events is critical for the microstructure and properties of the alloy. Studies on thermal transfer in the Inconel 718 alloy available in the literature typically focus on the alloy in its as-delivered state. The experimental research presented in this paper examines the influence of repeated overheating history on the thermal diffusivity of the alloy.